Annotated Repertoire of Bibliografía Musical Venezolana (Mayéutica Revista Científica de Humanidades y Artes, 2023)
Under the direction of the maestro Juan Francisco Sans, the Vicente Emilio Sojo Foundation embarked on the deepening of research and dissemination of Venezuelan and Latin American music, establishing strategic alliances with other institutions. Such is the case of the present study carried out in the Department of Music of the School of Arts of the Universidad Central de Venezuela, UCV, on the Venezuelan musical bibliography. This work received recognition from the Asociación Española de Documentación Musical, Aedom, in 1997.
Keywords: Universidad Central de Venezuela; Fundación Vicente Emilio Sojo; musicology; bibliography; research